Proceedings of the LST International Cohference on Geography and Education (ICGE 2016) 2017
DOI: 10.2991/icge-16.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Guided Inquiry to Critical Thinking Ability to Build Student Character in Geography Subject

Abstract: Abstract-Character is an important thing to consider in education. Characters that should be imparted to students in Indonesia contained in the standard of competence in 2013 curriculum. Teachers can build students character with using of learning models that includes character activities and critical thinking. Guided inquiry learning model can improve critical thinking and growing the students character through activities in a syntax's. The purpose of this paper discusses the effect of guided inquiry model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…According to Piaget (in Slavin, 1997), junior high school students are in the early stages of formal operations, so that children can use their concrete operations to form more complex operations and need to be guided by others. In addition, the provision of minimal or no guidance during instruction is usually less effective than the presence of sufficient guidance, there is also the possibility of negative results, for example, students gain misunderstanding or incomplete knowledge (Nurul H. et al, 2017). Therefore, student activities in learning will be maximized if delivered in an appropriate learning model such as a guided inquiry model.…”
Section: Introductionmentioning
confidence: 99%
“…According to Piaget (in Slavin, 1997), junior high school students are in the early stages of formal operations, so that children can use their concrete operations to form more complex operations and need to be guided by others. In addition, the provision of minimal or no guidance during instruction is usually less effective than the presence of sufficient guidance, there is also the possibility of negative results, for example, students gain misunderstanding or incomplete knowledge (Nurul H. et al, 2017). Therefore, student activities in learning will be maximized if delivered in an appropriate learning model such as a guided inquiry model.…”
Section: Introductionmentioning
confidence: 99%
“…The gain value in both classes is included in the high category. Hidayati et al (2017) suggest that students with analytical competence will be more competent and able to identify inferential relationships between statements, questions, concepts, and descriptions in expressing beliefs, judgments, experiences, reasons, and information. The posttest results show that the E-module with the ROPES strategy assisted by sigil software in learning can stimulate critical thinking skills on indicators of analyzing arguments.…”
Section: Resultsmentioning
confidence: 99%
“…Instrument testing was conducted in class XI Social Science 1. The instrument of essay questions was tested for validity with correlated bivariate SPSS 21.0 for Windows [49]. The test results showed that five essay questions had a significance of 0.000 on the total score.…”
Section: Methodsmentioning
confidence: 99%